2017
DOI: 10.3897/jhr.58.13253
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Rickia wasmannii (Ascomycota, Laboulbeniales) on the aggression and boldness of Myrmica scabrinodis (Hymenoptera, Formicidae)

Abstract: The interactions of ectosymbiotic Laboulbeniales (Ascomycota) fungi and their hosts are rather understudied. Rickia wasmannii Cavara is a common ant-associated Laboulbeniales species that has been reported in 17 countries of Europe, and frequently infects Myrmica scabrinodis Nylander, 1846 (Hymenoptera: Formicidae), a common ant species host, in high density. These make M. scabrinodis and R. wasmannii appropriate model organisms for studies on fungal host-ectosymbiont interactions. Aggressiveness and boldness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
10
2
Order By: Relevance
“…It is a common view that these fungi have little or no effect on their hosts (Benjamin 1971;Tavares 1985). Fitness effects have been estimated by a few controlled studies (Whisler 1968;Strandberg & Tucker 1974), as well as some insights into how these fungi may influence the behaviour of their hosts (Konrad et al 2014;Báthori et al 2017;Csata et al 2017). Their source of nutrients is debatable, but they are believed to draw them from their hosts through absorption or via contact with living tissues (Scheloske 1969;Benjamin 1971;Tavares 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It is a common view that these fungi have little or no effect on their hosts (Benjamin 1971;Tavares 1985). Fitness effects have been estimated by a few controlled studies (Whisler 1968;Strandberg & Tucker 1974), as well as some insights into how these fungi may influence the behaviour of their hosts (Konrad et al 2014;Báthori et al 2017;Csata et al 2017). Their source of nutrients is debatable, but they are believed to draw them from their hosts through absorption or via contact with living tissues (Scheloske 1969;Benjamin 1971;Tavares 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, laboratory based findings and field studies have shown that this fungal infection does not attack Myrmica larvae [11,21,24,25] , but is known to cause an array of detrimental changes in physiology in individual ant workers, such as a decrease in life expectancy, particularly in cases of water and food deprivation [15] , increased sanitary behavior [14] , and a reduced ability to fight against competitors [16,17] . Yet, despite the number of negative effects detected under laboratory conditions, infected colonies in the field have been thought to function relatively well, as they contain queens, larvae and pupae, and all age-classes of workers (see Csata et al [17] ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies on the physiological response of infected workers of the main host Myrmica scabrinodis Nylander, 1846, infected workers show higher mortality under laboratory conditions [14,15] . Infected M. scabrinodis workers were also shown to exhibit improved sanitary behavior [14] and a decreased level of intraspecific aggressivity [16,17] which may be disadvantageous for the infected colonies in competitive interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-known phenomenon that ants avoid or attack individuals from foreign colonies, whether of the same or a different species [ 2 , 28 ], which we have also experienced often with Myrmica ants in the lab [ 29 , 30 ]. Whether aggression takes place, and how strong it is, depends on multiple factors, including resource availability [ 31 , 32 ], territory or nest ownership [ 33 , 34 , 35 ], the presence of social and individual parasites [ 29 , 30 ], and recognition of intruders as being “non-self” [ 34 , 36 ], primarily through colony and species-level differences in cuticular hydrocarbons (CHCs) [ 37 ]. The level of aggression is generally directly and positively related to the dissimilarity between the CHCs of the colony and the intruders [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%